2017
DOI: 10.2134/jeq2017.03.0117
|View full text |Cite
|
Sign up to set email alerts
|

Biogas Digester Hydraulic Retention Time Affects Oxygen Consumption Patterns and Greenhouse Gas Emissions after Application of Digestate to Soil

Abstract: Knowledge about environmental impacts associated with the application of anaerobic digestion residue to agricultural land is of interest owing to the rapid proliferation of biogas plants worldwide. However, virtually no information exists concerning how soil-emitted NO is affected by the feedstock hydraulic retention time (HRT) in the biogas digester. Here, the O planar optode technique was used to visualize soil O dynamics following the surface application of digestates of the codigestion of pig slurry and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…Planar optodes have been used to investigate ammonium concentrations, diffusion, and transport in soil after fertilization [71,127,128]. The oxygen consumption and greenhouse gas emissions (mainly CO 2 ) in soils after were tested after amendment with organic fertilizers [129], and applications of digestate to soil [130] were previously monitored with PO sensors. An application of a SAW sensor functionalized with a polymeric coating (based on α,ω-dihydroxyalkyl lead(II)carboxylate complexes with 1,3-butadiene diepoxide as the co-monomer and 1,3,5-trihydroxybenzene as the reticulating agent) and a geophysical tool-ground penetrating RADAR (GPR)-to register sensor response, was reported to detect H 2 S in gas phase in a wireless configuration in soil and in real conditions (weather, temperature, and humidity) in [131].…”
Section: Other Compounds and Sensory Applicationsmentioning
confidence: 99%
“…Planar optodes have been used to investigate ammonium concentrations, diffusion, and transport in soil after fertilization [71,127,128]. The oxygen consumption and greenhouse gas emissions (mainly CO 2 ) in soils after were tested after amendment with organic fertilizers [129], and applications of digestate to soil [130] were previously monitored with PO sensors. An application of a SAW sensor functionalized with a polymeric coating (based on α,ω-dihydroxyalkyl lead(II)carboxylate complexes with 1,3-butadiene diepoxide as the co-monomer and 1,3,5-trihydroxybenzene as the reticulating agent) and a geophysical tool-ground penetrating RADAR (GPR)-to register sensor response, was reported to detect H 2 S in gas phase in a wireless configuration in soil and in real conditions (weather, temperature, and humidity) in [131].…”
Section: Other Compounds and Sensory Applicationsmentioning
confidence: 99%
“…Concerning the temperature regime, most investigations have been developed in the optimal temperature of the mesophilic regime (35 • C) [67,68]; see Table 3. It is important to mention that successful AD studies considering fruit and vegetable residues or swine slurry as substrates were found using temperature values lower than 20 • C [69,70]. In relation to CW, there are a few investigations, such as that developed by Yamashiro et al [71], that have studied two temperature regimes (mesophilic and thermophilic), although their objective was to make a digestate analysis to evaluate its final characteristics.…”
Section: Substrate MIXmentioning
confidence: 99%
“…Methane and carbon dioxide, which are the main components of biogas, add to the greenhouse gas effect if released from landfills, WWTPs or farms. This is the reason why it is essential that biogas be obtained under controlled conditions and used to generate thermal energy and electricity . This article contains a review of literature published recently (Figure S1), and an overview of various technologies employed in biogas production.…”
Section: Introductionmentioning
confidence: 99%
“…This is the reason why it is essential that biogas be obtained under controlled conditions and used to generate thermal energy and electricity. 30,31 This article contains a review of literature published recently (Figure S1), and an overview of various technologies employed in biogas production. This study describes both biological and physicochemical factors that can influence the process of biogas production.…”
Section: Introductionmentioning
confidence: 99%